Early diagnosis of necrotizing fasciitis. (29th November 2013) - Goh, T.; Goh, L. G.; Ang, C. H.; Wong, C. H.
Abstract : Background: Necrotizing fasciitis is a rapidly progressing skin infection characterized by necrosis of the fascia and subcutaneous tissue, accompanied by severe systemic toxicity. The objective of this systematic review was to identify clinical features and investigations that will aid early diagnosis . Methods: A systematic literature search of PubMed was undertaken using the keywords 'necrotising fasciitis', 'necrotising skin infection', 'diagnosis' and 'outcome'. Case series of 50 or more subjects with information on symptoms and signs at initial presentation, investigations and clinical outcome were included . Results: Nine case series were selected, with a total of 1463 patients. Diabetes mellitus was a co‐morbidity in 44·5 per cent of patients. Contact with marine life or ingestion of seafood in patients with liver disease were risk factors in some parts of Asia. The top three early presenting clinical features were: swelling (80·8 per cent), pain (79·0 per cent) and erythema (70·7 per cent). These being non‐specific features, initial misdiagnosis was common and occurred in almost three‐quarters of patients. Clinical features that helped early diagnosis were: pain out of proportion to the physical findings; failure to improve despite broad‐spectrum antibiotics; presence of bullae in the skin; and gas in the soft tissue on plain X‐ray (although this occurred in only 24·8 per cent of patients) . Conclusion: A high index of suspicion of necrotizing fasciitis is needed in a patient presenting with cutaneous infection causing swelling, pain and erythema, with co‐morbidity of diabetes or liver disease. The presence of bullae, or gas on plain X‐ray can be diagnostic. Early surgical exploration is the best approach in the uncertain case . Abstract : Speedy diagnosis imperative